2020
DOI: 10.1177/2150132720922714
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Motivational Interviewing Intervention to Improve Whole-Person Lifestyle

Abstract: The purpose of this randomized controlled trial was to examine the effects of a motivational interviewing intervention to improve whole-person lifestyle and reduce cardiovascular disease risk profile. A sample of 111 adults with type 2 diabetes and/or hypertension was recruited from a primary care physician practice. The intervention was facilitated by a program specialist trained in motivational interviewing. Outcomes included body mass index, cholesterol, hemoglobin A1c, blood pressure, waist circumference, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…And in terms of behavioral aspects of adherence intervention, our results showed some discrepancy between “Often” used patient‐centeredness and/or empowerment of patients and “Never” used motivational interviewing. Because these approaches are within the same spirit or principles, more formal education or training on the concept of motivational strategy or behavioral intervention would improve the quality of overall adherence interventions 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…And in terms of behavioral aspects of adherence intervention, our results showed some discrepancy between “Often” used patient‐centeredness and/or empowerment of patients and “Never” used motivational interviewing. Because these approaches are within the same spirit or principles, more formal education or training on the concept of motivational strategy or behavioral intervention would improve the quality of overall adherence interventions 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…The quantitative study findings showed statistically significant changes in BMI and waist circumference between the intervention and control groups at the 6-month follow-up (Sawyer et al, 2020). Also, the proportion of high total wellness scores, measured through self-reported data with the Wellness Evaluation of Lifestyle (WEL) (Myers et al, 2004), in the intervention group increased after the wholeperson lifestyle intervention (Sawyer et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Effective behavioural prevention strategies are also needed to reduce the growing burden of CVD. Considering the links between individual health behaviours and cardiovascular health, interventions that focus on health behaviours, such as diet, physical activity, and smoking, may improve associated health outcomes and reduce costs to the health care system (LeFevre, 2014;Morton et al, 2014;Sawyer et al, 2020;Spring et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations